Recent advances in quantum dot-based fluorescence-linked immunosorbent assays. Issue 12 (3rd March 2023) - Lv, Yanbing; Fan, Jinjin; Zhao, Man; Wu, Ruili; Li, Lin Song
Abstract : Quantum dot-based fluorescence-linked immunosorbent assays (QD-FLISAs) have been greatly developed in the field of in vitro diagnostics (IVD) and food safety due to their advantages of high sensitivity, high precision and high throughput. Abstract : Fluorescence immunoassays have been given considerable attention among the quantitative detection methods in the clinical medicine and food safety testing fields. In particular, semiconductor quantum dots (QDs) have become ideal fluorescent probes for highly sensitive and multiplexed detection due to their unique photophysical properties, and the QD fluorescence-linked immunosorbent assay (FLISA) with high sensitivity, high accuracy, and high throughput has been greatly developed recently. In this manuscript, the advantages of applying QDs to FLISA platforms and some strategies for their application to in vitro diagnostics and food safety are discussed. Given the rapid development of this field, we classify these strategies based on the combination of QD types and detection targets, including traditional QDs or QD micro/nano-spheres-FLISA, and multiple FLISA platforms. In addition, some new sensors based on the QD-FLISA are introduced; this is one of the hot spots in this field. The current focus and future direction of QD-FLISA are also discussed, which provides important guidance for the further development of FLISA.